Basic rules and stages of prepress preparation - Toksanova Асель (Рroblems of engineering and professional education, 2023)
This article discusses the main aspects of the pre-press layouts and methods of work in the graphic editors, Adobe InDesign, Adobe Illustrator, Corel Draw. The main requirements for printing. Getting ready to print.